Structural design of a lattice composite cantilever. (April 2019) - Solly, James; Früh, Nikolas; Saffarian, Saman; Aldinger, Lotte; Margariti, Georgia; Knippers, Jan
Abstract: The ICD/ITKE Research Pavilion 2016/2017 is the most recent in the series of experimental building demonstrators developed by the Institute for Computational Design (ICD) and the Institute for Building Structures and Structural Design (ITKE) at the University of Stuttgart. The completed structure is a 12 m long cantilevering lattice-composite shell that was wound in one piece by a multi-machine fabrication system using coreless filament winding. To realise such a structure through this fabrication process involved a negotiation between architectural design, structural requirements and fabrication constraints. The structural design process was divided into two steps. A shell model was used to evaluate possible geometries in the initial negotiation between architectural design and fabrication constraints. In order to approximate the highly anisotropic material behaviour of fibre reinforced polymers, substitute material properties had to be determined in physical tests. In the second step the actual fibre layup was analysed using a detailed beam-element model. The main load bearing fibre bundles were directly analysed in cross section and position. As-built and intended geometry were constantly compared and the feedback was used to refine the finite element analysis during fabrication. This paper covers the aspects mentioned and gives an outlook on further possibilities of this design and fabrication approach.